Seropositivity of influenza A H1NI in mothers and infants following maternal vaccination with trivalent seasonal influenza vaccine after the 2009 pandemic - An-Shine Chao; Yao-Lung Chang; Anne Chao; Ting-Shu Wu; Lan-Yan Yang; Reyin Lian; Yhu-Chering Huang (Elsevier, 2017)
Objective: To assess H1N1 antibody titers between vaccinated and nonvaccinated maternal and cord blood sera after the 2009 pandemic. Materials and Methods: Antibody titers were measured in maternal blood and cord sera from three groups of pregnant women in this prospective study. Group 1 comprised women who received a trivalent seasonal influenza vaccine before conception, Group 2 comprised women who received a single injection of monovalent H1N1 vaccine during pregnancy, and Group 3 comprised women who were nonvaccinated. A seropositive or seroprotective hemagglutination inhibition (HAI) assay was defined as titer ≥ 1:40. Results: In this study, 500 healthy women were enrolled, of which 44 women were in the trivalent seasonal influenza vaccine group, 41 women were in the monovalent vaccine group, and 415 women were in the nonvaccinated group. The seropositive HAI titers in the three groups of mothers were 48%, 78%, and 12%, respectively. The HAI titers in the vaccinated groups were significantly higher than those in the nonvaccinated group. The HAI titers of the cord blood samples of the three groups were comparable to their respective maternal samples. Conclusion: Seroprotection after the 2009 HIN1 pandemic was generally low in pregnant women. Vaccination during pregnancy yielded best seropositivity, whereas receiving a trivalent seasonal influenza vaccine before conception can offer better seroprotection to mothers and newborns than no vaccination.